(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
This article examines and describes the main changes in accounting and tax accounting that came into force on 01/01/2023. The new standard FSBU 14/2022 was considered. The author also analyzed the innovations in the budget and tax accounting of organizations on the formation of the tax base, studied innovations in the issue of changing special tax regimes. The scientific novelty and practical significance of the article lies in the assessment of the impact of the main changes in the field of accounting and tax accounting of organizations in the current 2023.